ANALISIS PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN PROVIDER XL PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS RIAU KEPULAUAN, BATAM - Bakkara, Arfiyanti; Wibowo, Edwin Agung (BENING, 2016)
This research intents to know â€œDo service quality, and price affect to customer loyalty XL products at the Faculty of Economics, Riau Kepulauan University, Batam?". The purpose of this study to analyze the effect of each variable, the quality of service (X1), and the price (X2) to customer loyalty (Y). In this study, data were collected through questionnaires to 43 respondents XL product users in the Faculty of Economics, Riau Kepulauan University using purposive sampling method to determine the response of respondents to each variable with using program application Statistical Product and Service Solution (SPSS) version 20. Then analyze the data obtained in the form of quantitative analysis and qualitative analysis. Quantitative analysis include validity and reliability test, the classic assumption test, hypothesis testing via the F test and t test and analysis test, the coefficient of determination (R2.Results of the analysis found that two factors service quality and price has positive and significant influence on customer loyalty. Hypothesis testing using t test showed that independent variables service quality found to significantly affect customer loyalty as dependent variables, while independent variables price found not significantly affect customer loyalty as dependent variables . Through the F test showed that the variable service quality and price has a significant jointly in customer loyalty. Figures adjusted R square of 0.501 indicates that 50.1 % of the variations of customer loyalty can be explained by five independent variables used in the regression equation. The rest of 49.9 % is explained by another variable outside two variables used within this research.Â Keywords: service quality, price, customer loyalty.